Geopolitic Reconstruction of Religion (Learning from Hurgronje in Religion versus Government Conflict Management) - Moersidin, Murry Darmoko; Mumtaz, Nadhif Muhammad; Salsabila, Ayna Jamila; Alu Hasan, Khalid Ibrahim; Sholihaturrahmaniah, Isna (Graduate School of UIN Syarif Hidayatullah Jakarta, 2022)
Political expression of religion can be dangerous for good governance system. And this has really happened in Indonesian history, both during the Dutch occupation and when Indonesia became independent. Religion has become a political vehicle in various forms of political parties and non-parties. Religion also caused military wars which resulted in heavy casualties. The research questions are: What are the factors that turn religion against the government? How did Hurgronje resolve the religious versus government conflict? The approach is carried out with the Sociology of Religion. This paper uses the IMRAD style. Materials obtained through documents and internet news media. The method used is qualitative. The Results: religion as a political doctrine will lead to conflict religion and government and through three groupings of the role of religion in the right portion, ala Hurgronje, will enable the government to reduce conflict